Comparison of drying processes for the production of raisins from a seedless variety of grapes - Almeida, Inês (2013)
Drying is a very important preservation method that originates products with high nutritive value, among which the raisins, which are a very popular food product consumed worldwide. The objectives of the present work were to dry by different processes seedless grapes from variety Crimson, which is not traditionally used for the production of raisins. Furthermore, to compare the different methods tested, some analyses were made, namely at the chemical, physical and sensorial levels. The methodologies tested for the drying of the grapes were: direct exposure to the sun inside a solar stove and ventilated drying chambers with constant air flow at two different temperatures, 50 and 60 ºC. The technological parameter evaluated for the different dryings was the yield. At the chemical level were evaluated the moisture content, total sugars and acidity. In terms of physical properties were assessed the texture and colour, fundamental aspects for a good acceptation of dried products by the consumers. Lastly, a sensorial analysis was made to the dried products obtained, aimed at evaluating their acceptability by potential consumers. The raisins produced by the different methods didn´t show important differences either at the chemical or at the physical levels. Still, some aspects can be pointed out: the convective drying method allowed obtaining products with less moisture and in considerably less time, reaching 14.59 % in 47 hours for the drying at 60 ºC, while in the solar stove was obtained 19.43 % of humidity during 721 hours of drying. This result is very important from the economic point of view. Finally, at the sensory level, the tasters considers that the dried grapes produced in this work showed similar characteristics with some commercial raisins at sale in the Portuguese market.